Catalog of Chilean Pentatominae Leach, 1815 (Hemiptera: Heteroptera: Pentatomidae) - Faúndez, Eduardo I.; Carvajal, Máriom A. (Zootaxa, 2011)
The Chilean Pentatominae species are listed and catalogued; a total of 18 species have been accounted. Additionally 3 species present doubtful or incomplete records. Most of the species are endemic to South America; 2 species are considered introduced in Chile, and 6 species are exclusively Chilean.